A prebiotically plausible synthesis of pyrimidine β-ribonucleosides and their phosphate derivatives involving photoanomerization - Xu, Jianfeng (Nat Chem, 2016)
Previous research into the prebiotic synthesis of the pyrimidine nucleotides has revealed a potential intermediate with remarkable properties – ribose aminooxazoline crystallises spontaneously from reaction mixtures, and with an enhanced enantiomeric excess if initially enantioenriched. This automatic chemical and chiral purification suggests that reservoirs of this compound in optically pure form might have accumulated on the early Earth. Studies have shown that ribose aminooxazoline can be efficiently converted to α-ribocytidine by way of 2,2'-anhydro-ribocytidine, though anomerization to β-ribocytidine by UV irradiation is extremely inefficient. Our previous work demonstrated the synthesis of pyrimidine β-ribonucleotides, but at the cost of ignoring ribose aminooxazoline and using arabinose aminooxazoline instead. Here, we describe a long sought route through ribose aminooxazoline to the pyrimidine β-ribonucleosides and their phosphate derivatives, that involves an extraordinarily efficient photoanomerisation of α-2-thioribocytidine. In addition to the canonical nucleosides, our synthesis accesses β-2-thioribouridine, a modified nucleoside found in tRNA and which enables both faster and more accurate nucleic acid template copying chemistry.